Forever young – why we still love vampires in the 21st century. - Lima, Maria Antónia (2015)
Forever young – why we still love vampires in the 21st century. The astonishingly enduring influence of the vampire myth on many young people today is a phenomenon that reveals the relevance of one of the nineteenth century's most powerful surviving archetypes, which never seems to fade. Yet since Bela Lugosi's portrayal of Bram Stoker's Dracula, the figure of the vampire has undergone many transformations; in recent years, this is thanks to Anne Rice's Vampire Chronicles and other works such as Elizabeth Kostova’s The Historian and Stephanie Meyers’s Twilight series. While seeking to avoid turning the study of vampires into a trendy pursuit, we strive to achieve a broader understanding of how pervasive the vampire tale currently is in world culture and why this may be so at this particular time, interested as we are in images of eternal youth and discovering what the vampire myth can tell us about sexuality, power, alienation, sickness, evil, loneliness and death. Vampirism, not just as a looming presence in the night, but as a symbol of our own human insecurities and desires for love, justice and freedom, we may conclude, like Nina Auerbach in Our Vampires, Ourselves, “springs not only from paranoia, xenophobia, or immortal longings, but from generosity and shared enthusiasm. This strange taste cannot be separated from the expansive impulses that make us human." In their search for a lost sense of humanity that makes them feel like lost souls in an era of crisis, it is only natural that young people see in the image of the vampire the reflection of themselves, and find an archetype for their identity as humans and one of the most plausible answers to the question of what it means to be human. Through blood legends recreated in literature, films and art, they are transported to a place where they feel close to their origins, where they can find meaning for their lives. In a century which is permeated by economic uncertainty, we need to be reassured that “The Blood is the life!” (Bram Stoker, Dracula).